A Study of Nietzsche's Concept of Ubermensch in David and Uriah by Abbas Nalbandian - Mohammad Exir (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Seasoning his dialogues with politics, philosophy and various other subjects, Abbas Nalbandian presents his argument about the mirage of truth through poetic and literary expressions. Although Nalbandian has been influenced by Western philosophers and playwrights, he has been successful in localizing such influences in his works. Reading David and Uriah from the perspective of the Nietzschean Ubermensch shows that not only does Nalbandian transform this concept into an artistic work, but also he uses it both as an ideological springboard and a structural element in organizing his play. The present paper emphasizes the importance of reading David and Uriah through a Nietzschean interpretive framework and explores the role that Nietzsche’s thought plays in this work. The methodology is, therefore, comparative and interdisciplinary. We discuss the ways in which Nietzsche’s idea contributes to a new understanding of David and Uriah’s main character and the play’s artistic form. Moreover, the paper shows he ways inwhich this knowledge provides readers with a better understanding of the playwright as an artist and an individual. The findings of this study demonstrate how Nalbandian, by drawing on Nitzchean philosophy, has localized and appropriated the concept of Ubermensch in David and Uriah and, thus, enriched Persian literature.